Об одной задаче сближения для колебательных систем - Чикрий, Г.Ц. (Теорія оптимальних рішень, 2005)
The problem of soft meeting of two controlled oscillatory systems is treated. Sufficient conditions for pursuit termination in a finite time are obtained. An explicit formula for control of the pursuer is derived, under special condition for finding “tracks” of the evader.